Conceptual model of social-ecological resilience in Mexican forests communities - Solís-Mendoza, Lesly Elizabeth; Galicia, Leopoldo; Ávila-Foucat, Sophie Véronique; Mwampamba, Tuyeni Heita (Frontiers in Forests and Global Change, 2025)
The social-ecological forest systems of central Mexico are essential for delivering a variety of contributions of nature that benefit both local and global communities, however, these forests are under increasing threat from climate change, market globalization, and outmoded forest policies. This paper examines the resilience of these social-ecological forest systems, focusing on their ability to adapt to such challenges. We utilized the grounded theory method, which combines quantitative and qualitative data from existing literature and empirical knowledge about the structure and functioning of forests and human communities. Then, we developed a dynamic system conceptual model to describe the cause-effect processes of forest disturbances and resilience capacities integrating qualitative interdisciplinary information to establish causal links and adaptive strategies. Our conceptual model identifies forest disturbances threatening Mexican forests, key structural elements and dynamic interactions within these systems, specifically governance system (social processes), contributions of nature (ecological processes), and forest management (social-ecological processes) promoting the resilience. By analyzing the effects of climate change and globalized markets we aimed to uncover the factors that enhance or undermine resilience in these systems, for example, climate change adversely affects species richness, soil properties, and economic diversification, creating a feedback loop that diminishes ecosystem resilience. On the other hand, polycentric governance, biodiversity maintenance, and the control of slow-changing variables like nutrient recycling in forest soils are crucial for long-term forest management. We propose several strategies for enhancing resilience, for example, including the implementation of mixed forest plantations and community nurseries with native species to address climate change impacts. While globalized markets tend to favor the intensification and specialization of timber production, which reduces economic diversification, our research suggests that promoting multi-purpose forest harvesting and preserving other contributions of nature are essential for maintaining biodiversity and supporting local livelihoods.